Hypertension Accompanied by Hyperaldosteronism, Hyperkalemia, and Hyperchloremic Acidosis: A Case Report and Literature Review - Yunyun Yang; Yang Ou; Yan Ren; Haoming Tian; Tao Chen (Case Reports in Endocrinology)
This study reported on a 24-year-old woman who complained of a paroxysmal headache for six months and elevated blood pressure for four months. Laboratory examination revealed increased serum potassium and chloride levels, metabolic acidosis, suppressed renin activity, and increased plasma aldosterone concentration. Whole-exome sequencing revealed a heterozygous mutation in exon 11 of the KLHL3 gene: c.1298G > A. After treatment with low-dose hydrochlorothiazide, her clinical problems were controlled. This patient is the first case of Gordon syndrome (GS) within the Chinese population caused by a heterozygous KLHL3 mutation. A systematic review of the published literature identified 27 patients with GS caused by a KLHL3 mutation. These patients had a mean age of 28.2 ± 22.0 years; 74.1% presented with hypertension, 76.9% with hyperkalemia, and 59.1% with metabolic acidosis. The patients also had varying levels of plasma renin activity and plasma aldosterone concentrations.